CEAS Aeronautical Journal An Official Journal of the Council of European Aerospace Societies - Henke, Rolf.; SpringerLink (Online service) (Vienna : Springer Vienna : Imprint: Springer.)
The CEAS Aeronautical Journal has been created under the umbrella of CEAS to provide an appropriate platform for excellent scientific publications submitted by scientists and engineers. The German Aerospace Center (DLR) and the European Space Agency (ESA) support the Journal. The Journal is devoted to publishing results and findings in all areas of aeronautics-related science and technology as well as reports on new developments in design and manufacturing of aircraft, rotorcraft, and unmanned aerial vehicles. Of interest are also (invited) in-depth reviews of the status of development in specific areas of relevance to aeronautics, and descriptions of the potential way forward. Typical disciplines of interest include flight physics and aerodynamics, aeroelasticity and structural mechanics, aeroacoustics, structures and materials, flight mechanics and flight control, systems, flight guidance, air traffic management, communication, navigation and surveillance, aircraft and aircraft design, rotorcraft and propulsion. The Journal publishes peer-reviewed original articles, (invited) reviews and short communications.
Keywords: Aerospace engineering; Astronautics; Aerospace Technology and Astronautics